2005
DOI: 10.1182/blood-2005-06-2584
|View full text |Cite
|
Sign up to set email alerts
|

The combination of the farnesyl transferase inhibitor lonafarnib and the proteasome inhibitor bortezomib induces synergistic apoptosis in human myeloma cells that is associated with down-regulation of p-AKT

Abstract: The identification of signaling pathways critical to myeloma growth and progression has yielded an array of novel agents with clinical activity. Multiple myeloma (MM) growth is IL-6 dependent, and IL-6 is secreted in an autocrine/paracrine fashion with signaling via the Ras/Raf/mitogen-activated protein kinase (MAPK) pathway. We hypothesized that combining a Ras pathway inhibitor (lonafarnib, SCH66336) with a proteasome inhibitor

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 42 publications
1
34
0
Order By: Relevance
“…We did not see decreased Akt phosphorylation with bortezomib alone at synergistic concentrations, which may be due to either cell linespecific effects or dose differences. Combining proteasome inhibitors with other agents, such as the farnesyl transferase inhibitor lonafarnib or the cyclin-dependent kinase inhibitor flavopiridol, also down-regulates phosphorylated Akt (39,40). Therefore, Akt seems to play a central role in mediating the cytotoxicity of proteasome inhibitors in combination with a diverse group of therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…We did not see decreased Akt phosphorylation with bortezomib alone at synergistic concentrations, which may be due to either cell linespecific effects or dose differences. Combining proteasome inhibitors with other agents, such as the farnesyl transferase inhibitor lonafarnib or the cyclin-dependent kinase inhibitor flavopiridol, also down-regulates phosphorylated Akt (39,40). Therefore, Akt seems to play a central role in mediating the cytotoxicity of proteasome inhibitors in combination with a diverse group of therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…5 In vitro co-treatment with proteasome inhibitors removes resistance and increases sensitivity to different types of anticancer drugs, including traditional antiblastics and g-irradiation, 2,3 as well as more novel therapeutics such as rituximab, histone deacetylase inhibitors, farnesyl transferase inhibitors, tyrosine kinase inhibitors and the cyclin-dependent kinase inhibitor flavopiridol (Bisping G et al Blood 2005; 106: 112; abstract). [24][25][26][27][28] In this context, we have demonstrated that proteasome inhibitors synergistically interact with recombinant TRAIL to overcome chemoresistance and induce apoptosis in chemoresistant Bcl-2-overexpressing lymphoma cells. 23 Interestingly, the cytotoxic effects of proteasome inhibitors have repeatedly been observed to depend on active protein synthesis within the cell, as the translation inhibitor cycloheximide typically blocks proteasome inhibitor-induced apoptosis at a very upstream stage.…”
Section: Mechanisms Of Anticancer Activity Of Proteasome Inhibitorsmentioning
confidence: 99%
“…With a wide range of investigational drugs that exploit essential PTM events commonly required by many tumors, combination therapy is being used with various other forms of treatment. These include the use of various PTM inhibitors with chemotherapeutic adjuvants such as taxanes, nucleoside analogs, and platinum agents (70 -72); radiation therapy (73); combination therapy with estrogen receptor antagonists (53); and finally combinations of drugs that inhibit different forms of PTM (74,75). In several cases prolongation of patient survival was found when these combination therapies were used.…”
Section: Ptms In Cancer Treatmentmentioning
confidence: 99%